2009
DOI: 10.1177/172460080902400108
|View full text |Cite
|
Sign up to set email alerts
|

Elevated CA 19-9 Levels in Mature Cystic Teratoma of the Ovary

Abstract: The purpose of this study was to evaluate the clinical value of serum tumor markers in patients with ovarian mature cystic teratoma (MCT). We retrospectively evaluated 163 women who underwent surgery for MCT of the ovary between March 2003 and August 2007 and who provided preoperative blood samples for the measurement of CA 19-9 and CA 125. The rates of elevated serum CA 19-9 and CA 125 levels were 31.9% (52/163) and 13.5% (22/163), respectively. The rate of ovarian torsion was 12.9% (21/163). There were signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 20 publications
2
27
0
Order By: Relevance
“…This retrospective investigation found that CA 19-9 and CA 125 levels were elevated in 31.9% and 12.5% of cases, respectively. In addition, CA 19-9 levels correlated with larger tumor diameters and elevated torsion rates [1]. Abiding by Kyung et al's [1] hypothesis, our patient also exhibited large tumor size, significant torsion, and high CA 19-9 level (2179.62 U/mL).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…This retrospective investigation found that CA 19-9 and CA 125 levels were elevated in 31.9% and 12.5% of cases, respectively. In addition, CA 19-9 levels correlated with larger tumor diameters and elevated torsion rates [1]. Abiding by Kyung et al's [1] hypothesis, our patient also exhibited large tumor size, significant torsion, and high CA 19-9 level (2179.62 U/mL).…”
Section: Discussionsupporting
confidence: 75%
“…In 2009 a study by Kyung et al [1] hypothesized that CA 19-9 could be a predictor of ovarian torsion and the extent of cystic necrosis. This retrospective investigation found that CA 19-9 and CA 125 levels were elevated in 31.9% and 12.5% of cases, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been widely studied and reported in association with mature cystic teratomas of the ovary where unusually high levels have been reported [7][8][9].…”
Section: Discussionmentioning
confidence: 99%